Studi Penambatan Senyawa Dari Tanaman Kembang Bulan (Tithonia Diversifolia (Hemsley) A.Gray) Terhadap Peroxisome Proliferator-Activated Receptor-Gamma (PPARɣ) Untuk Penyakit Diabetes Melitus - Nur Rahma Rumata; Nursamsiar Nursamsiar; Maghfirah Putri Arifin (STIFA Makassar, 2022)
Diabetes mellitus is a disease whose prevalence continues to increase both in the world and developing countries, so it is said that diabetes mellitus is a problem for global public health. One of the receptors that play a role in stimulating insulin storage so that resistance does not occur is the PPARƔ receptor. The purpose of this study was to simulate the interaction of moonflower compounds with several proteins at the PPARƔ receptor in the design of antidiabetic drugs by molecular docking method. The docking results showed that all moonflower compounds could interact with the active site of PPARƔ. The ligands with the best interactions were indicated by compounds with the best interactions shown by compounds 27, compounds 29 and compounds 31 with binding energy values, respectively, namely, -8.03 kcal/mol, -6.85 kcal/mol, -8.20 kcal/mol. Meanwhile, Thiazolidinediones as a positive control showed G value of -9.71 kcal/mol. These results indicate that the compound T. diversifolia is predicted to have potential as antidiabetic therapy.